1964 (2020)
Adriana Mejía lee el poema. 1964 del poeta argentino Jorge Luis Borges. Imagen tomada de: https://derechoareplica.org/index.php/mas/criminologia/1225-borges-y-una-criminologia-de-buenos-aires